Penerapan Model Pembelajaran Problem Based Learning (PBL) Untuk Meningkatkan Motivasi Dan Hasil Belajar Siswa Pada Materi Sitem Ekskresi Manusia - Arni Arni (LPPM Politeknik Pratama, 2023)
This research was conducted to increase student interest and learning outcomes in this material using discussion methods and the Problem Blended Learning (PBL) learning model. This research was conducted to find out what methods are appropriate for teaching by teachers in the classroom. The research method used in classroom action research (Classroom Action Research) is observation, the research process is carried out in two cycles, the previous action being carried out in the pre-cycle stage, each cycle includes 4 stages, namely: 1) planning stage, 2) implementation stage, 3) stage observation, 4) reflection stage. The results obtained from the research showed that there was an increase in learning motivation seen from the indicators of student activity in the question and answer session in the 2021/2022 academic year in the first cycle, only 32.14% of students in one class were active, in the second cycle there was an increase, where students who Initially only 32.14% of students in one class were active, increasing to 60.71% of students in one class who were active in asking questions. Meanwhile, the timeliness indicator for collecting assignments in the implementation of PTK this time from data for the 2020/2021 academic year in the first cycle was 71.42% of students, in the second cycle there was an increase to 96.42% of students in one class. In the indicator for the number of scores above the KKM, the data obtained in the 2020/2021 academic year in the first cycle was 46.43% of students in one class, in the second cycle there was an increase to 71.42%.